Estados de humor, concentrações de cortisol e desempenho técnico-tático de atletas de alto rendimento do voleibol de praia - Torres, Vitor Bruno Cavalcanti (2018)
In the context of sports performance, the search for progress that favors performance is a constant challenge for technical commissions and researchers who investigate indicators of the game, and in other aspects who contribute to success, such as psychosocial and hormonal factors. In this sense, the objective of the present study was to analyze the mood states, salivary cortisol concentration and technical-tactical performance of the Brazilian high-income adult beach volleyball male athletes in the competition environment. Initially a systematic review about the relevant scientific productions was carried out on the relationships of psychometric scales, cortisol concentrations and their interactions with athletic performance in high performance in collective sports. After applying the inclusion and exclusion criteria, only 10 studies were cataloged. As results, the application of salivary collection seems to be quite pertinent in this type of study, on the performance a great part of the studies emphasizes only losing and gaining, however it requires a more in depth analysis on the performance taking into account the individuality. it's about a study descriptive, cross-sectional, observational, quantitative and correlational research. The population was composed of 32 high-yield beach volleyball athletes. For the sample, we investigated 14 male athletes, adults, participants of the competitions organized by the Brazilian Volleyball Confederation. The first collection was held in the morning, the athletes arriving at the event arena were being approached. Then, the POMS questionnaires were completed. In order to collect the salivary cortisol, before heating (pre) for the first game the first saliva of the athletes was collected in the interval between 08:30 and 09:30. At the end of the first match the athletes provided saliva for the second collection between 10.30 and 11.30 (post). In order to collect data on the game, six camcorder cameras were used at the bottom of the court so that the images fit the entire block for analysis of technical-tactical performance (efficacy and coefficient). Pearson correlation, t-test for independent samples and repeated-measure ANOVA were used. A significance level of 5% was established in all tests. In the technical-tactical performance, significant differences between success and failure group were observed in the drawdown error (p = 0.038) and in the efficacy of the attack (p = 0.002), already in the cortisol concentrations, 6,368, p = 0.020) with higher values in both variables for successful athletes. There were no significant differences between the groups in the pre-competition mood states. It is concluded that the athletes' experiences seem to interfere in the states of humor, as well as the presence of a balance in the actions, being the terminal actions relevant to the final result of the match. It is too early to say but it seems that high concentrations of cortisol have influenced the final outcome of the match, with higher values for successful teams.